PHYSICOCHEMICAL PROPERTIES OF THE KEITH AND JULIE VARIETIES OF MANGO (MANGIFERA INDICA L) IN YOLA, NIGERIA - Abdullahi, D. M. Kirawa; Tame, V. T; Jakusko, B. B (Research Journal of Agriculture (RJA), 2024)
Mango (Mangifera indica L), a climacteric tropical and sub-tropical fruit, has numerous health-related benefits. The physicochemical characteristics and proximate composition of mango fruits are useful for classifying mango varieties and understanding the benefits that could be derived from the fruits. There is a lack of information on the characteristics of Keith and Julie mango varieties in Nigeria. This study was carried out at the Department of Crop Production and Horticulture of Modibbo Adama University, Yola, to determine the physicochemical properties of fresh Keith and Julie mango fruits. The mango fruit were harvested on the orchard of the University at the matured green stage when they had clear, well-developed shoulders at the stem end. Data on the fruits were collected, including firmness, size, and weight pH, total soluble solids, trivial acidity, moisture content, carbohydrate, protein, fat, ash, crude fiber, dry matter, energy value, and vitamins. The results of the physicochemical properties showed that significant differences (P≤0.05) existed among the varieties with the Keith variety having higher levels of in some characters like total soluble solids (19.45ᵒBrix) than Julie variety which had 13.90ᵒ Brix. Similarly, Julie had higher values in some characters like moisture content (83.67- 83.85%), Protein content (0.70 - 0.71), and vitamin C (52.87- 55.00 mg/100 g) when compared to Keith, who had moisture content of 79.30-84.00%, protein content of 0.13-0.28%, and vitamin C of 47.33 – 49.61 mg/100 g. These differences affect the taste, storability, and nutritional values derivable from the consumption of these fruits. may be the result of varietal differences, which could be consistent and diverse. These results may be useful to researchers interested in mango varietal improvement. It also provides information on maturity and taste indices, which are useful for those involved in the processing industry.